2018
DOI: 10.17925/eoh.2018.14.1.45
|View full text |Cite
|
Sign up to set email alerts
|

The Belarus Experience of Pelvic Artery Embolisation in Patients with Advanced and Recurrent Cervical Cancer Presenting with Haemorrhage

Abstract: To determine the efficacy of pelvic artery embolisation (PAE) in patients with locally advanced and recurrent cervical cancer (CC) complicated by haemorrhage, a retrospective study was performed of 81 patients with locally advanced or recurrent CC who underwent PAE for haemorrhage. Of the 81 patients included in the study, 68 (84%) had primary locally advanced CC and 13 (16%) had recurrent disease. Distribution of patients with primary disease according to the International Federation of Gynecology and Obstetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Femoral, axillar, brachial, or radial artery are catheterized during endovascular therapy [ 9 , 17 ]. There are various agents used for embolization, such as metallic coils, glue, spheres, gel-foam particles, gelatin sponge particles, polymer microspheres, polyvinyl alcohol particles or a combination of these [ 1 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Femoral, axillar, brachial, or radial artery are catheterized during endovascular therapy [ 9 , 17 ]. There are various agents used for embolization, such as metallic coils, glue, spheres, gel-foam particles, gelatin sponge particles, polymer microspheres, polyvinyl alcohol particles or a combination of these [ 1 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding occurring from advanced cervical cancer may appear in up to 70% of cases and is the immediate cause of death in 6% of patients with this kind of malignancy [ 15 , 16 ]. In case of emergency intractable bleeding, arterial embolization of branches of the internal iliac arteries represents a promising alternative [ 14 , 17 , 18 ]. Bilateral embolization should be performed due to collateral pelvic vasculature [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple studies that have shown the role of selective pelvic-vessels embolization in cervical cancer ( Table 3 ). 4 , 9 , 11 - 17 …”
Section: Discussionmentioning
confidence: 99%